Variation in menarcheal age of school-aged female athletes engaged in different types of sport - Tatarczuk, Józef; Wandycz, Artur; Malinowski, Andrzej (Anthropological Review, 2019)
It is widely known from the literature that the rate of physical development and sexual maturation is not only determined by genetics but is also modified by physical workload factors. Given the above, this paper aimed at comparing menarcheal age of school-aged athletes engaged in different types of sport (and their respective workloads) after controlling for physical traits such as body height and mass and slenderness ratio. The survey was conducted in 2017 in 6 sports schools in Poland’s Lubuskie Voivodeship. Body height and mass were measured and the slenderness index (body height divided by the cubic root of body weight) was used to establish body build. The age of menarche was self-reported by the study participants. In total, 232 girls aged 9–18 were included in the research, of whom 125 reported their age of menarche. The age-adjusted arithmetic means and standard deviations were calculated for the study participants’ estimates. The raw data were then transformed into standardized z-score values. The significance of differences was assessed by Mann-Whitney U test as an alternative to the t-test when a given variable was not normally distributed. Pearson’s correlation coefficient was used to evaluate linear relations between the workload and age at menarche. It was found that dancers, acrobats and swimmers reported the youngest menarcheal ages. Girls practising most demanding sport disciplines (in terms of strength and endurance) reported the oldest age at menarche. Girls practising more than 3 times per week had menarche later than those practising 3 times a week or less, and the difference was statistically significant. In conclusion it might be stated that the type of sport discipline has a significant effect on age of menarche. Sport disciplines involving heavier physical exertion usually delay the onset of menstruation.